Person and environment - Hutchison, Elizabeth D (Sage Publications, 2008)
Includes bibliographical references (p. 505-561) and index.; Aspects of human behavior : person, environment, time / Elizabeth D. Hutchison -- Theoretical perspectives on human behavior / Elizabeth D. Hutchison and Leanne Wood Charlesworth -- The biological person / Stephen French Gilson -- The psychological person : cognition, emotion, and self / Joseph Walsh -- The psychosocial person : relationships, stress, and coping / Joseph Walsh -- The spiritual person / Michael J. Sheridan -- The physical environment / Elizabeth D. Hutchison -- Culture / Linwood Cousins -- Social institutions and social structure / Elizabeth D. Hutchison -- Families / Nancy R. Vosler -- Small groups / Elizabeth P. Cramer -- Formal organizations / Elizabeth D. Hutchison -- Communities / Elizabeth D. Hutchison and Soon Min Lee -- Social movements / Elizabeth D. Hutchison.; Neal A. Newfield, Ph.D., LICSW (Giver)